2012
DOI: 10.1254/jphs.12086sc
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Hydrogen Sulfide^|^ndash;Induced Visceral Pain and Referred Hyperalgesia Involve Activation of Both Cav3.2 and TRPA1 Channels in Mice

Abstract: Abstract. Luminal hydrogen sulfide (H 2 S), a gasotransmitter, causes colonic pain / referred hyperalgesia in mice, most probably via activation of T-type Ca 2+ channels. Here we analyzed the mechanisms for H 2 S-induced facilitation of colonic pain signals. Intracolonic administration of NaHS, an H 2 S donor, evoked visceral pain−like nociceptive behavior and referred hyperalgesia in mice, an effect abolished by NNC 55-0396, a selective T-type Ca 2+ -channel blocker, or by knockdown of Ca v 3.2. AP18, a TRPA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 14 publications
2
31
2
Order By: Relevance
“…In contrast to the results obtained with intraplantar injections of NaHS, intracolonic administration of NaHS produced identical nociceptive effects in Trpa1 +/+ and Trpa1 −/− mice, suggesting that although TRPA1 stimulation is essential for the somatic pronociceptive effects of H 2 S, it is not required for the visceral effects of H 2 S. It is worth noting that administration of vehicle itself produced a significant nociceptive response, as reported by others [10], [29]. Previous studies have demonstrated a referred mechanical hyperalgesia following colonic instillation of NaHS in mice [10], [29]. Here, we found no difference between the sensitivity to abdominal stimulation with von Frey filaments between mice treated with vehicle and NaHS and the mechanical sensitivity was virtually identical in Trpa1 +/+ and Trpa1 −/− mice (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…In contrast to the results obtained with intraplantar injections of NaHS, intracolonic administration of NaHS produced identical nociceptive effects in Trpa1 +/+ and Trpa1 −/− mice, suggesting that although TRPA1 stimulation is essential for the somatic pronociceptive effects of H 2 S, it is not required for the visceral effects of H 2 S. It is worth noting that administration of vehicle itself produced a significant nociceptive response, as reported by others [10], [29]. Previous studies have demonstrated a referred mechanical hyperalgesia following colonic instillation of NaHS in mice [10], [29]. Here, we found no difference between the sensitivity to abdominal stimulation with von Frey filaments between mice treated with vehicle and NaHS and the mechanical sensitivity was virtually identical in Trpa1 +/+ and Trpa1 −/− mice (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…10] and genetic silencing of TRPA1 (Okubo et al, 2012). The role of TRPA1 in H 2 S-induced visceral pain, however, remains controversial, with one group finding similar pain behavior in wild-type and Trpa1 knockout mice and another group reporting the involvement of both TRPA1 and Ca v 3.2 channels in H 2 S-induced colonic pain and referred hyperalgesia (Tsubota-Matsunami et al, 2012).…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%
“…TRPA1 receptors are partially responsible for mechanosensitive responses of afferent neurons in mouse colon (12,13). Recent evidence suggests that H 2 S acts on TRPA1 directly in colonic afferent neurons to enhance nociceptive function (110).…”
Section: Lindenmentioning
confidence: 99%